Aplikasi Pupuk Phospat Dan Giberelin (Ga3) Untuk Meningkatkan Produksi Benih Gambas (Luffa Acutangula (L.) Roxb) - Baidowi, Moch; Sulistiyono, Nantil Bambang Eko (Agropross : National Conference Proceedings of Agriculture, 2023)
Even while luffa hasn't yet established itself as a valuable product in Indonesia, it has the potential to provide a variety of advantages. The selection of inappropriate seeds is one of the deep problems for squash cultivators. The application of Phospat and Giberellin fertilizers as a cultivation technique is carried out to increase the production of luffa seeds to meet the needs of seeds in Indonesia. This research was conducted from September 2022 to March 2023 in road rice fields. Toba Lake 7, Sumbersari, Regency. Jember. Using a factorial randomized block design (RBD) with 3 replications. The first factor was phosphate fertilizer (0, 25 and 30 g/tan) and the second factor was the concentration of gibberellin (Ga3) (0.200 and 300 ppm). Data were analyzed using Analysis of Variance (ANOVA) at 5% and 1% levels, then tested with Duncan's Multiple Range Test (DMRT) at 5% level. The results showed that phosphate fertilizer (SP36) produced a very significant difference in the number of branches on days 21 and 35 after planting, which were 4.27 and 5.56, the male flowering days were 24.89 and the number of seeds per fruit was 30.37(items). The application of giberellin (Ga3) gave a very significant difference in the parameters of many branches, namely 5.24 and 6.13, the days of female flowering were 24.22, the length of the fruit was 27.90(cm), and the diameter of the fruit was 4.57(cm).